STUDI DESKRIPTIF PEMANFAATAN DANA DESA DI KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA TAHUN 2015 - B2053151006, FITRIYANI (Jurnal Ekonomi Daerah (JEDA), 2017)
The aim of this research is to describe the effective use of the Village Fund in tree villages in the kecamatan Sungai Kakap and also to knows the barriersÂ  or constraints thats faced by the society on making of village planning. This research using descriptive method. In collecting data, researchers use interviewing techniques, observation and documentation that determined by using the qoute sampling technique and purposive sampling technique.The results of this research present that the effective use of the village fund fiscal year 2015 in two villages in the Kecamatan Sungai Kakap have effective implementation according to the Regulation of the Ministry of Village, Development of Disadvantaged Regions, and Transmigration No. 5 of 2015, While in one village in the kecamatan Sungai Kakap the implementation is not effective because the program activities carried out not based with Permendes PDTT No. 5/2015. The barriers/constraints faced by the society in the preparation of village planning are their proposals not realized in the form of programs especially on infrastructure of the village.The results from this research is Village officials have to really learn and understand more about the guidelines/reference/basic implementation of village funds that issued by the central government and local government as well as to disseminate more depth to the public so that the public can understand the rules and regulations. Â  Keywords:Effective, Utilization of the village fund